PENGARUH DINAMIKA INTERNAL DAN EKSTERNAL UNI EMIRAT ARAB DALAM PENGAMBILAN KEBIJAKAN NORMALISASI UNI EMIRAT ARAB-ISRAEL - SYAIFUL ANAM; Amalia Hasanah (Jisiera: The Journal of Islamic Studies and International Relations, 2023)
This research analyzes how United Arab Emirates (UAE) internal and external settings affect the UAE's decision to normalize its diplomatic ties with Israel. Snyder, Bruck, and Sapin's foreign policy theory of internal-external setting is used to analyze this research. For the research methodology, qualitative methods are used, with most of the data coming from secondary sources. This research ascertains that several internal and external settings play a significant role in the normalization. For instance, two internal settings are affecting this policy. First, The UAE security threat comes from its position as a small country sandwiched between the two most considerable regional powers. Second, The shift in UAE's public opinion toward Israel's sovereignty. As for the External setting, three factors play a crucial role in this decision. First, the polarization in the middle east makes it easier for UAE to secure its safety by taking a side. Second, diplomatic normalization between Qatar and Iran is changing the dynamic in the middle east, bringing a potential threat to UEA. Third, Trump endeavors to get US allies in the Middle East closer to Israel by proposing Trump Peace Plan. Trump's Peace Plan provides a pretext for UAE to normalize its ties with Israel without seemingly putting Palestinian issues under the bus.